Green carbon materials : Advances and applications - Rufford, Thomas; Jurcakova Denisa hulicova; Zhu John (Singapore : PSP, 2014)
Agricultural and food industry waste materials have been an important feedstock for activated carbon production for many years. In the development of cleaner energy production and utilization processes, new advanced carbon materials with enhanced properties have been studied. Techniques to tailor pore structure and surface chemistry can produce better carbon materials for energy storage, electrode materials, and selective adsorption of pollutants. This book surveys available waste materials and processes for carbon production and then reviews the recent developments in the use of carbon materials for energy storage, as catalyst supports, and for environmental applications.
Index 283-288p.
Keywords: Adsorption of volatile organic vapours; Green chemistry applications of nanoporous carbons; Removal of toxic gases on activated carbons; Absorbed natural gas and hydrogen storage